2015
DOI: 10.1111/hepr.12541
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic expression of N‐acetylglucosaminyltransferase V accelerates hepatic triglyceride synthesis

Abstract: Aim: Glycosylation changes induce various types of biological phenomena in human diseases. N-Acetylglucosaminyltransferase V (GnT-V) is one of the most important glycosyltransferases involved in cancer biology. Recently, many researchers have challenged studies of lipid metabolism in cancer. To elucidate the relationships between cancer and lipid metabolism more precisely, we investigated the effects of GnT-V on lipid metabolism. In this study, we investigated the effects of aberrant glycosylation by GnT-V on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…These and our current results suggest HBP and N-glycan branching interact descriptively as a thrifty phenotype 52 . Moreover, Mgat5 transgenic mice displayed increased body-weight and liver to body-weight ratio 53 , along with increased hepatic lipogenesis characterized by elevated Fasn, Acc and Srebp-1 gene expression 54 . Conversely, Mgat5 −/− mice are resistant to weight-gain on 9% fat diet, and display hypersensitivity to fasting with greater glycogen depletion and hypoglycemia 19 , essentially an opposing phenotype compared to GlcNAc-supplemented wild-type mice in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…These and our current results suggest HBP and N-glycan branching interact descriptively as a thrifty phenotype 52 . Moreover, Mgat5 transgenic mice displayed increased body-weight and liver to body-weight ratio 53 , along with increased hepatic lipogenesis characterized by elevated Fasn, Acc and Srebp-1 gene expression 54 . Conversely, Mgat5 −/− mice are resistant to weight-gain on 9% fat diet, and display hypersensitivity to fasting with greater glycogen depletion and hypoglycemia 19 , essentially an opposing phenotype compared to GlcNAc-supplemented wild-type mice in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, recent genome-wide CRISPR screens in HAP1 cells revealed correlated essentiality between fatty acid synthase (FASN) and multiple N-glycosylation enzymes, indicating a role for ER and Golgi pathways in lipogenesis (19). Transgenic mice overexpressing either glutamine: fructose-6P-aminotransferase (Gfpt) in the HBP or Golgi Mgat5 in the liver display obesity, steatosis, impaired glucose tolerance and insulin resistance (20,21).…”
Section: Introductionmentioning
confidence: 99%
“…Briefly, recent genome-wide CRISPR screens in HAP1 cells revealed correlated essentiality between fatty acid synthase (FASN) and multiple N-glycosylation enzymes, indicating a role for ER and Golgi pathways in lipogenesis (19). Transgenic mice overexpressing either glutamine: fructose-6P-aminotransferase (Gfpt) in the HBP or Golgi Mgat5 in the liver display obesity, steatosis, impaired glucose tolerance and insulin resistance (20, 21). Conversely, Mgat5 deficient mice are resistant to weight gain on a high fat diet (22), similar in this regard to wild type mice on a high fat diet in which branched chain amino acids (BCAA: Leu, Ile, Val) have been reduced (23).…”
Section: Introductionmentioning
confidence: 99%
“…GnT-V promotes cancer metastasis by enhancing growth factor signaling, integrin function, and expression of certain kinds of proteases (17,31,32). Very recently, we found that enhancement of hepatic GnT-V activity accelerates triglyceride synthesis (14). We also reported that GnT-V suppressed nonalcoholic steatohepatitis (NASH) progression in a mouse NASH model (16).…”
mentioning
confidence: 99%